Identifying patterns of care for elderly patients with non-surgically treated stage III non-small cell lung cancer: an analysis of the national cancer database - Eric D Miller; James L Fisher; Karl E Haglund; John C Grecula; Meng Xu-Welliver; Erin M Bertino; Kai He; Peter G Shields; David P Carbone; Terence M Williams; Gregory A Otterson; Jose G Bazan (Radiation Oncology, 2018)
Abstract Background To compare patterns of care for elderly patients versus non-elderly patients with non-surgically treated stage III non-small cell lung cancer (NSCLC) using the National Cancer Database (NCDB). We hypothesize that elderly patients are less likely to receive curative treatments, including concurrent chemoradiation (CCRT), compared to non-elderly patients. Methods We identified patients from the NCDB between 2003 and 2014 with non-surgically treated stage III NSCLC. We defined elderly as ≥70 years old and non-elderly <70 years old. Treatment categories included: no treatment, palliative treatment (chemotherapy alone, radiation (RT) alone <59.4 Gy or chemoradiation (CRT) <59.4 Gy), or definitive treatment (RT alone ≥59.4 Gy or CRT ≥59.4 Gy). Differences in treatment between elderly and non-elderly were tested using the χ2 test. Results We identified 57,602 elderly and 55,928 non-elderly patients. More elderly patients received no treatment (24.5% vs. 13.2%, P < 0.0001) and the elderly were less likely to receive definitive treatment (48.5% vs. 56.3%, P < 0.0001). CCRT was delivered in a significantly smaller proportion of elderly vs. non-elderly patients (66.0% vs. 78.9%, P < 0.0001 in patients treated with definitive intent; 32.0% vs. 44.5%, P < 0.0001 in patients receiving any treatment; and 24.2% vs. 38.6%, P < 0.0001 amongst all patients). Conclusions In this large study of patients with non-surgically treated stage III NSCLC, elderly patients were less likely to receive any treatment or treatment with definitive intent compared to the non-elderly. The lack of use of concurrent or sequential chemotherapy in the elderly with stage III NSCLC suggests that the optimal treatment approach for this vulnerable population remains undefined.